Revitalisasi dan Pemberdayaan Fakultas Ushuluddin dan Dakwah: Kajian Atas Pengembangan Fak. Ushuluddin dan Dakwah IAIN Sultan Maulana Hasanuddin Banten - Mohamad Hudaeri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2014)
Faculty of Islamic Theology and Communication have an important position as a scientific core or basic sciences in Islamic study that have a strategic role both in the development of Islamic knowledge or in character building. However, it is a reality, Theology is a faculty that has fewer students than other faculties. But in fact, they had good quality. In this regard, the revitalization and empowerment at the facultyof Islamic Theology is an urgent matter. The article is focused on the search and analyze the existence of the Islamic Theology and communication department of Islamic State of Sultan MaulanaHasanuddin, both in terms of its strengths and weaknesses, as well as the expectations and the challenges it faced. Therefore, thisstudy included internal institutional and academic aspects and society's view toward the existence of the Islamic Theology and Communication Department.